Immune checkpoint inhibitor-induced anti-Hu antibody-associated gastrointestinal pseudo-obstruction: a case report and literature review - Shi, Guang-Qing; Lian, Heng-Ning; Wang, Xue; Xia, Jie-Qiang; Wang, Huan; Ma, Li-Jie; Xiao, Zhen-Liang; Zhou, Jing (Frontiers in Immunology, 2025)
The immune checkpoint inhibitors (ICIs)-induced anti-Hu antibody-associated gastrointestinal pseudo-obstruction (GIPO) is a paraneoplastic neurological syndrome related to autoantibodies. It has a very low incidence but a high mortality rate. This report presents the case of a patient with extensive-stage small-cell lung cancer who developed recurrent bowel obstruction symptoms following ICI therapy. Colonoscopy and abdominal CT tomography failed to identify the underlying cause. A definitive diagnosis of GIPO was made based on the histological findings from an exploratory laparotomy and serum levels of paraneoplastic antibodies. Despite treatment with corticosteroids, no significant improvement was detected in the symptoms, and the patient ultimately died. This case highlights the challenges of managing this rare complication. When unexplained bowel obstruction occurs during ICI therapy, antineuronal antibody testing should be performed to exclude GIPO, as early identification and intervention can reduce mortality.